Recent advances in semitransparent perovskite solar cells. Issue 1 (9th October 2020) - Mujahid, Muhammad; Chen, Chen; Zhang, Jian; Li, Chuannan; Duan, Yu
Abstract: The environmental challenges across the world step up the researcher's interest in different energy resources. Semitransparent perovskite solar cells (ST‐PSCs) could expedite generation of electricity as well as shows reassuring its significance in flexible electronics and building‐integrating photovoltaic as so forth in the next decade. It is highly recommended to endorse the relevance of semitransparent solar devices to fulfill the required level of energy even by using the roofs and windows of the buildings. In this review article, we pay more attention to recent developments of ST‐PSCs. Herein, a succinct overview of latest research about semitransparent solar cell technologies and ST‐PSCs is summarized. Moreover, the strategies to enhance the transparency of solar cells are described utilizing structure, transparent electrodes, perovskite film formation, tandem solar cells, color tuning, and human eye perception. Last but not least is that the serious concerns about stability of ST‐PSCs are vividly reviewed. Abstract : Semitransparent perovskite solar cells show its significance in flexible electronics and building integrating photovoltaic. We review various overview of latest research about semitransparent solar cell technologies. Moreover, the strategies the transparency of solar cells are described utilizing structure, transparent electrodes, perovskite film formation, tandem solar cells, color tuning, and human eye perception. Further, the concerns about stability of semitransparent perovskite solar cells are also commented in the review.